Please Don't! The Automatic Extrapolation of Dangerous Intentions - Tessari, Alessia (Public Library of Science, 2012)
Facial emotions and emotional body postures can easily grab attention in social communication. In the context of faces, gaze has been shown as an important cue for orienting attention, but less is known for other important body parts such as hands. In the present study we investigated whether hands may orient attention due to the emotional features they convey. By implying motion in static photographs of hands, we aimed at furnishing observers with information about the intention to act and at testing if this interacted with the hand automatic coding. In this study, we compared neutral and frontal hands to emotionally threatening hands, rotated along their radial-ulnar axes in a Sidedness task (a Simon-like task based on automatic access to body representation). Results showed a Sidedness effect for both the palm and the back views with either neutral and emotional hands. More important, no difference was found between the two views for neutral hands, but it emerged in the case of the emotional hands: faster reaction times were found for the palm than the back view. The difference was ascribed to palm views' “offensive” pose: a source of threat that might have raised participants' arousal. This hypothesis was also supported by conscious evaluations of the dimensions of valence (pleasant-unpleasant) and arousal. Results are discussed in light of emotional feature coding.